EVALUATION BREAD WHEAT PURE LINES UNDER EFFECT OF DIFFERENT SEEDING RATES - & Naes, Baktash (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research was carried out at the Swerah Research Station –Office of Agricultural Researches during  2014-2015 seasons. The objective of this research was evaluation bread wheat  (Triticum aestivum L.) genotypes ,which concluded 15 pure lines in seventh generation, which developed by half dialld method between 6 parents ,The experiment was conducted using split plot arrangement with RCBD design with three replicates ,The main plots content four seeding rates (120, 160, 200 and 240 kg.ha-1 ), while the 21 genotypes occupied sub plots .The two pure lines S97 and S148 superoired to all other genotypes except A4.10 and Abu-Ghraib  in grain yield which, produced 6.35 and 6.09 t.ha-1 .Increasing seeding rates caused early flowering, increased plant height, biological yield and harvest index. Significant differences were found in all the studied characters due to genotypes and seeding rates interaction. The pure line S148 ,using 200 kg.ha-1 seeding rates produced highest grain yield (7.49 t.ha-1).